Enhancing bipartite entanglement through OPA coupled to squeezed vacuum reservoir in an optomechanical system - Sisay Belachew (ASTU, 2022)
The aim of this thesis is to Enhancing bipartite entanglement through OPA coupled to squeezed vacuum reservoir in an optomechanical system. The Hamiltonian of system derived as entanglement between a cavity field and a movable mirror filled with an optical parametric amplifier coupled to squeezed vacuum resersoir interacts with a nonlinear crystal inside a cavity. By using Heisenberg equations of the sys tem, the dynamics of optomechanical system incorporating new features, obtained based on the linearized quantum Langevin equations. On the other hand the dissipa tion, quantum noise, fluctuation terms and covariance matrix are obtained by using the quantum Langevin equations. Moreover, the entanglement of optical parametric amplifier coupled to squeezed vacuum reservoir are quantifying by using logarithmic negativity. It is found that the presence of optical parametric amplifier coupled to squeezed vacuum reservoir enhancing entanglement of the cavity radiation. Thus, when an squeezed vacuum reservoir is added inside a cavity, the optomechanical coupling and the entanglement are improved
Keywords: Optomechanical system, Entanglement, OPA, Sqeezed vacuum reservoir, Logarithmic negativity